Complexity pattern of center of pressure between genders via increasing running speed - Ryu, J. (Korean Journal of Sport Biomechanics, 2019)
Objective: The goal of this study was to determine the center of pressure (CoP) complexity pattern in approximate entropy technique between genders at different conditions of running speed.